Konstruksi Pengetahuan Ibu balita Stunting Dalam Menyikapi Fenomena Stunting di Desa Jatisari (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
This main objective of this study is to understand how the knowledge construction of mothers of stunted toddlers develops in response to the stunting phenomenon in Jatisari Village. In the context of this study, qualitative methods are used with a phenomenological approach and social construction theory by Berger & Luckman (year) as the main analytical tool to explore this phenomenon in depth. During the data collection process, several steps were carried out;observation of the village environment, interviews with mothers of toddlers, and collection of related documentation. The results of the study revealed a number of underlying causes of stunting that emerged in Jatisari Village. These factors coverthe community's low level of education, economic constraints affecting access to nutrition, inappropriate eating patterns, and knowledge gaps between health workers and residents. In addition, data analysis showed variations in the knowledge construction of mothers of stunted toddlers in Jatisari Village. Findings in the field identified two different forms of knowledge among research informants. Most mothers of these toddlers only consider stunting as a technical term that describes a short or thin child's physique. Meanwhile, three other informants had a deeper understanding of stunting, admitting that this is an indicator of children malnutrition that requires serious attention. Through this research, it was revealed how the perceptions and knowledge of mothers of stunted toddlers in Jatisari Village were gradually formed in response to the complex phenomenon of stunting. These findings provide valuable insights into how to approach and address this serious problem more effectively in rural communities. Keywords: knowledge construction, mothers of stunted toddlers, stunting phenomenon, Jatisari village.